Role of Customs Legislation and Practice of Its Implementation in the Protection of Fauna of Ukraine (Law and Safety, 2021)
The article is focused on studying the role of legislation and state policy in the customs sphere in ensuring the preservation of wildlife in Ukraine in the context of the possibility of exporting samples of wild animals outside Ukraine. The main problems of prevention of illegal seizure of wild fauna samples for their further movement outside Ukraine have been identified.The main factors influencing the impossibility of preventing the export of wild animals outside Ukraine are the state policy on simplification of customs clearance of goods and the introduction of the “single window” principle. Those mechanisms themselves do not create the preconditions for the movement of illegally seized wild animals across the border. However, the lack of mechanisms for the exchange of information between customs and veterinary authorities and environmental authorities leads to a lack of mechanisms for environmental authorities to respond to the facts of illegal removal of wild animals from the environment. In turn, customs and veterinary authorities are deprived of the powers to control the legality of the origin of wild animals to be moved across the border of Ukraine.The author has emphasized the need to develop automated algorithms for the exchange of information on the movement of wild animals across the border between the relevant government agencies in order to further control the legality of the origin of animals and bring to justice those who illegally released wild animals.The results of the study can be used in the practice of customs legislation in order to establish mechanisms to prevent illegal movement of wild animals across the state border and bring to justice those guilty of removing animals from the environment in violation of the current legislation of Ukraine.
Keywords: customs law; customs legislation; customs clearance; the Customs, wild animals.